The grotesque body in Ian McEwan’s short stories - Moghadam, Nahid Shahbazi; Termizi, Arbaayah Ali (University of Oslo, Department of British and American Studies, 2017)
The subject matter and imagery prevalent in Ian McEwan’s early fiction are shockingly unpleasant and justifiably notorious for their portrayal of grotesqueries to the extent that their significance has been ignored or undermined compared to his later more successful works. In the present study, we discuss these grotesque representations and their implications in a number of his short stories from the two collections of In Between the Sheets (1975) and First Love, Last Rites (1978). Our discussion of the grotesque body in the aforementioned stories relies on a synthesis of Mikhail Bakhtin’s notion of grotesque realism and John R. Clark’s view of the modern satiric grotesque, which involves grim laughter and degradation reinforced through scatological imagery. We thus argue that the loss of a communal and regenerative sense of human existence in the modern life style can explain the sadism, masochism, violence or fatality prevalent in contemporary fiction as exemplified in McEwan’s short stories.